Effects of di(2-etilhexil) phthalate on human umbilical artery. (August 2019) - Azevedo, R.; Oliveira, N.; Maia, C.; Verde, I.
Abstract: Di(2-etilhexil) phthalate (DEHP) is a compound used in plastic materials, which has endocrine disrupting properties. The human DEHP exposure depend on the use of plastics in toys, medical devices and food and beverage containers. The DEHP effects were studied in some physiological systems; nevertheless, the actions in human arteries were never described. We analysed the DEHP effect on endothelium denuded human umbilical artery (HUA), an important artery to ensure gases and nutrients exchange with fetus. We assessed DEHP short-term effects on contractility, occurring few minutes after DEHP is in contact with HUA in the organ bath receptacles. The long-term effects on HUA, observed after 24 h in presence of DEHP, were assessed in the organ bath system, and also through the analysis of receptors expression (5-HT2A and H1 ) and of cellular viability, by using HUA smooth muscle cells. DEHP (1 nM-100 μM) induced a short-term relaxing effect on HUA contracted by 5-HT, histamine or KCl. DEHP long-term exposure of arteries (1 nM, 10 μM and 100 μM) reduced its own relaxant effect on HUA contracted by 5-HT and histamine and, precisely, 24 h exposure to DEHP 1 nM reverted the relaxant effect on 5-HT contractility. Long-term exposure at more than 10 nM of DEHP decreased 5HT2A receptors expression. In conclusion, DEHP short-term exposition elicit vasodilation of HUA contracted by different agents. DEHP long-term exposition reduced the expression of 5HT2A receptors. The DEHP long-term exposition decrease the short-term relaxant effect and, at low concentrations can increase the contractile effect of 5-HT. Highlights: DEHP relax human umbilical arteries under the influence of 5-HT, histamine or a depolarizing condition. The long-term exposition to DEHP causes reduction in the expression of 5HT2A receptors. The long-term action of DEHP on HUA reduces the short-term vasodilator effect of this endocrine disruptor.